Dampak Kebijakan Full Day School Pada Tingkat Sekolah Dasar - Andi Rahmaeni; Kasmawati Kasmawati (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
The focus of this study is to gather information on how the Full-day school policy impacts learning in elementary schools. This study uses a qualitative approach and combines a comprehensive literature review from electronic sources and traditional print media, including online books and journals. The research methodology uses documentation from various sources, including literature, treatises, essays, scientific papers, journals, and magazines. To evaluate the credibility and dependability of their findings, the researchers used the triangulation method by using various data sources. To conduct a comprehensive literature review, this study uses a four-step approach. This process includes data collection, data reduction, data presentation, and drawing conclusions. The results of the discussion and data analysis indicate that the implementation of the five-day school policy in elementary education has both good and bad effects.